Christianity and Fraternal Globalisation - de Aviz, Darlan Aurélio (Religions, 2023)
This paper discusses the importance of fraternity in building more fair and humane societies. The globalised world poses new challenges to the understanding of fraternity, especially when it is seen as an attack on the dignity of each person. Religions are considered to have an important role to play in responding to the dehumanisation that a certain type of globalisation can promote. To this end, we reflect on the threats and opportunities that the globalised world offers and how religious thought can make a positive contribution. Based on Pope Francis’ challenges, we will respond to what the “something greater” is that fraternity has to offer the world. The answer is developed using sources from the sacred scripture and the patristics to understand Christianity, where it is concluded that the model of relationships between people, in the thought of the magisterium in the light of sacred scripture, aims to awaken the awareness of a social friendship, which will grow to the extent that one offers what is best for the other, simply by loving them and being who they are.